(untitled) (Analysis in Theory and Applications, 2017)
With the aid of Mullin-Rota's substitution rule, we show that the Sheffer-type differential operators together with the delta operators Δ and D could be used to construct a pair of expansion formulas that imply a wide variety of summation formulas in the discrete analysis and combinatorics. A convergence theorem is established for a fruitful source formula that implies more than 20 noted classical formulas and identities as consequences. Numerous new formulas are also presented as illustrative examples. Finally, it is shown that a kind of lifting process can be used to produce certain chains of (∞^m) degree formulas for m≥ 3 with m1 (mod 2) and m1 (mod 3), respectively.